Práctica profesional Escuela José María Roy - Batista Guerra, Yazmina María (UDELAS, 2009)
The importance of this work is to reproduce the journey of a degree in teaching english from the perspective of learning by using the vrious skills acquired durind this time and including the students in developing themselves so they can see opportunites offered by english as a secon languaje.